Trade in banking services and the role of GATS - De Leon, Ernando S.; San Pedro, Teodora I. (The Philippine Review of Economics, 2003)
The General Agreement on Trade in Services (GATS), which was concluded by participating countries in the Uruguay Round of negotiations, is the first multilateral effort to establish rules governing the conduct of international trade in services, including financial services. The GATS also provides the framework for multilateral negotiations on improved market access for foreign services and service suppliers. This article aims to clarify the issues regarding the consequences of liberalizing trade in banking services and the obligations assumed by member countries in the context of negotiations under the GATS. It argues that the benefits of liberalizing trade in banking services arise primarily from greater competition and better financial intermediation. It also points out the interdependence between sound macroeconomic management, appropriate financial regulation and supervision and a liberal trade regime in banking services.